Qualitative Approach Dominates Character Education Research in History Education Journals in Indonesia - Rahfit Syahputra; Fini Fajri Mulyani (Journal of Innovation in Educational and Cultural Research, 2025)
Based on preliminary studies, studies that examine the significance of the impact related to a program, method, model, media, learning resources, and the like to improve student character are still rare. This study aims to evaluate the information found in articles about character education in Indonesia. The research design uses content analysis. The instruments used are aspects and categories related to research type, quantitative, and qualitative research type. The research instrument was modified from Susetyarini and Fauzi. The research findings show that in the last five years, research on character education has fluctuated but increased significantly in 2023. During this period, the dominant study design used was qualitative. The descriptive type was in the highest position, followed by historical research, while quantitative research was rarely applied. In terms of treatment, the articles analyzed have yet to find the application of a particular learning model, method, or technique in improving students' character. Based on these results, quantitative research is still rarely applied in studying character education. It is intended that other researchers, particularly those using quantitative methods, can use the findings to detect problems in studying character education, specifically the influence/correlation of certain variables on improving student character.